(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
A new chitosan derivative was prepared by grafting a ligand [3-(4methoxyphenyl)-1H-pyrazole-4-carbaldehyde] to chitosan by a Schiff base reaction. The chitosan-ligand derivative (CTSL) was characterized by spectral studies (FT-IR, 13CNMR, XRD) and scanning electronic microscope. The suitability of CTSL as an adsorbent for the removal of two metals viz. Cu (II) and Pb (II) was studied by conducting equilibrium, kinetic and thermodynamic studies. Experimental data obtained in equilibrium studies were analyzed for Langmuir, Freundlich, and Redlich-Peterson isotherms. The maximum monolayer adsorption capacity obtained for the two metals were CTSL-Cu (40.62 mg/g) and CTSL-Pb (71.99 mg/g). The data obtained from the kinetic study was analyzed with three models viz. pseudo-first order, pseudo-second order and intraparticle diffusion models. The pseudo-second-order rate equation fitted the experimental data very well. Thermodynamic parameters Î”G, Î”H and Î”S were determined. The sorption operation was feasible, exothermic and accompanied with a positive increase in entropy. The metal interactions with the adsorbent were attributed to the hydroxyl, imine and the amine groups present in the synthesized derivative.